Healthy helpers: using culinary lessons to improve children’s culinary literacy and self-efficacy to cook - Policastro, Peggy; Brown, Alison H.; Comollo, Erin (Frontiers in Public Health, 2023)
Children do not eat the recommended amounts of vegetables, and school-based nutrition education has not been found to impact this behavior. Cooking education is associated with improved children's culinary literacy (CL) and eating behaviors. This study investigated the impact of a culinary literacy (CL) curriculum on children's acceptance of vegetable-added (mushrooms) recipes, CL, self-efficacy to cook (SE), and willingness to try vegetables (WV). A convenience sample of 39 fourth and fifth graders was exposed to a six-lesson virtual CL curriculum that taught basic cooking skills and how to prepare six recipes, including three traditional recipes and the same recipes with added vegetables. Children who participated in the CL curriculum accepted vegetables added to pizza pockets, but vegetables added to macaroni and cheese and fajitas negatively affected the acceptance of recipes. Children improved their CL and SE, but did not show a significant change in their WV. Findings suggest that CL programs focusing on vegetables may drive factors associated with dietary behavior change, SE, and acceptance of vegetables. Future studies should consider CL as a potential method to improve vegetable intake in children in tandem with nutrition education or as a sole intervention. The study was limited by its small sample size and the fact that it was conducted in a virtual setting and only used mushrooms as the vegetable source. Future studies should be conducted with a larger sample size, in a more traditional classroom setting, use a variety of vegetables, and collect qualitative data on the sensory characteristics affecting children's WV.